Ishwardas Nagar's Futuhat-i-Alamgiri - Ishwardas Nagar; Ahmad, Tasneem, 1948- (Delhi : Idaeah-i Adabiyat-i Delli, 1978)
An account of the reign of Aurangzib, Emperor of Hindustan, 1619-1707.
Translated from Persian.
Includes bibliographical references and index.
Keywords: Aurangzeb, -- Emperor of Hindustan, -- 1618-1707.; Mogul Empire -- Kings and rulers -- Biography; Mogul Empire -- History